In-vitro-digestion of a controlled release material: composite aerated gel containing egg white protein - SRUN, Marnick; HIRUNSORN, Pimnibha; WACHIRATTANAPONGMETEE, Kwanruedee; PITIRIT, Theparit; THAWORNCHINSOMBUT, Supawan (Food Science and Technology, 2023)
This study aimed to produce a healthy jelly-like product containing protein and bioactive ingredient. Egg white protein (EWP: 0, 3, 6% w/w) and sucrose (0 and 7.5% w/w) were mixed at fixed levels of konjac glucomannan, κ-carrageenan, and sodium bicarbonate in an aerated gel preparation. An interaction between EWP and sucrose significantly yielded lower gas hold-up capacity exhibiting less and small pores confirmed by SEM images. The 3% EWP with 7.5% sucrose gel was selected to further study in vitro digestion by incorporating rice bran hydrolysate (RBH) and determining phenolic compound bioaccessibility. Syneresis and gas hold-up capacity of the gel was improved due to aeration and RBH (P<0.05). Aeration also enhanced the bioaccessibility of phenolic compounds and antioxidants after digestion. Therefore, this study introduces a new food matrix which is an aerated gel containing egg white protein that exhibits high bioaccessibility following pancreatic digestion.